2005
DOI: 10.1177/10598405050210020401
|View full text |Cite
|
Sign up to set email alerts
|

An Integrative Review of Interventions for Adolescent Weight Loss

Abstract: The number of overweight adolescents aged 12-19 has tripled during the past 2 decades. Although health risks associated with obesity in adolescence and adulthood are well documented in the literature, little is known about the efficacy of interventions to reduce health risks of this group. The purpose of this study was to conduct a systematic review to describe the scope, domain, and effectiveness of weight loss interventions with overweight adolescents. English-language journal articles published in nursing, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…11,12 In addition, MexicanAmerican youth simultaneously navigate the cultures of Mexico and the United States, leading to intergenerational struggles of acculturation within families. 13 Research has revealed the importance of generational status and acculturation of the adolescent and family on nutritional intake, quality of food choices, food preparation, obesity status, and food insecurity.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 In addition, MexicanAmerican youth simultaneously navigate the cultures of Mexico and the United States, leading to intergenerational struggles of acculturation within families. 13 Research has revealed the importance of generational status and acculturation of the adolescent and family on nutritional intake, quality of food choices, food preparation, obesity status, and food insecurity.…”
Section: Discussionmentioning
confidence: 99%
“…While results of a recent review of evidence suggest that parents can act as agents of change in interventions which target younger children and adolescents 28 , little is known about the impact of including parents and family in interventions with older adolescents 29, 30 . And while children and younger adolescents may need parents to make or help them make healthy eating and physical activity decisions, older adolescents may prefer to assert their autonomy and make their own decisions.…”
Section: Implications For Research and Practicementioning
confidence: 99%
“…In a recent review, Stuart et al 144 provide an in-depth analysis of treatment studies that targeted adolescent obesity and reviewed studies that met the following criteria: 1) were published between 1980 to 2003; 2) employed a minimum of 2 comparison groups, with an intervention designed to effect weight loss, and 3) enrolled participants between ages of 11 and 19 years. Initially, the authors intended to conduct a meta-analysis.…”
Section: Behavioral Treatment Strategiesmentioning
confidence: 99%
“…The studies ranged from 12 to 20 weeks. The interventions varied from lifestyle changes with/without family member involvement, lifestyle changes with and without exercise, the use of monetary reward structures, telephone and mail-based behavioral intervention, and an intervention with metformin as an adjunct to behavioral therapy, diet and exercise 144 . Most of the studies used group interventions (13 out of the 17), 2 studies used an individual, nongroup intervention for behavioral change 145,146 and 2 studies used physiologic interventions (metformin or low-carbohydrate/low fat diet; 147,148 .…”
Section: Behavioral Treatment Strategiesmentioning
confidence: 99%